Investigating the long-term legacy of statin therapy - Takata, Kohei; Psaltis, Peter J.; Nicholls, Stephen J. (Journal of Thoracic Disease, 2017)
For more than a quarter century, statins have been the predominant pharmacological approach to lowering levels of low-density lipoprotein cholesterol (LDL-C). On the basis of successive clinical trials, their use has expanded, spanning a wide range of cardiovascular risk. Despite their widespread use, there continue to be many unanswered questions with regard to understanding how these agents impact the natural history of atherosclerosis. As the seminal trials of statin therapy were performed more than 20 years ago, there is a unique opportunity to determine the long-term impact of these agents on cardiovascular outcomes in order to investigate potential legacy effects. In particular, such analyses permit evaluation of the long-term effects of relatively finite statin treatment on both cardiovascular outcomes and safety.